Accumbens brain‐derived neurotrophic factor (BDNF) transmission inhibits cocaine seeking. (11th June 2018) - Bobadilla, Ana‐Clara; Garcia‐Keller, Constanza; Chareunsouk, Victoria; Hyde, Jeffrey; Medina Camacho, Daniela; Heinsbroek, Jasper A.; Kalivas, Peter W.
Abstract : Brain‐derived neurotrophic factor (BDNF) regulates a variety of physiological processes, and several studies have explored the role of BDNF in addiction‐related brain regions like the nucleus accumbens core (NAcore). We sought to understand the rapid effects of endogenous BDNF on cocaine seeking. Rats were trained to self‐administer cocaine and extinguished. We then microinjected two inhibitors of BDNF stimulation of tropomyosin receptor kinase B (TrkB), the non‐competitive receptor antagonist ANA‐12 and TrkB/Fc, a fusion protein that binds BDNF and prevents TrkB stimulation. Blocking TrkB or inactivating BDNF in NAcore potentiated active lever pressing, showing that endogenous BDNF tone was present and supplying inhibitory tone on cue‐induced reinstatement. To determine if exogenous BDNF also negatively regulated reinstatement, BDNF was microinjected into NAcore 15 minutes before cue‐induced reinstatement. BDNF decreased cocaine seeking through TrkB receptor binding, but had no effect on inactive lever pressing, spontaneous or cocaine‐induced locomotion, or on reinstated sucrose seeking. BDNF‐infusion potentiated within trial extinction when microinjected in the NAcore during cue‐ and context + cue induced reinstatement, and the inhibition of lever pressing lasted at least 3 days post injection. Although decreased reinstatement endured for 3 days when BDNF was administered prior to a reinstatement session, when microinjected before an extinction session or in the home cage, BDNF did not alter subsequent cued‐reinstatement. Together, these data show that endogenous BDNF acts on TrKB to provide inhibitory tone on reinstated cocaine seeking, and this effect was recapitulated by exogenous BDNF. Abstract : We investigated the effect of endogenous brain‐derived neurotrophic factor (BDNF) secretion on cocaine seeking in the NAcore and discovered that BDNF‐induced tropomyosin receptor kinase B (TrkB) signaling during cued‐reinstatement promoted within session extinction and decreased cocaine seeking. We were able to pharmacologically recreate the inhibition of cocaine seeking by acutely microinfusing BDNF in the NAcore before cue‐induced reinstatement. This effect was specific to cocaine seeking and did not alter inactive lever pressing, spontaneous or cocaine‐induced locomotion, or sucrose seeking.